Between military non-alignment and integration: Finland and Sweden in search of a new security strategy - Tobias Etzold; Christian Opitz (Stiftung Wissenschaft und Politik (SWP), 2015)
Alarmed by the Ukraine crisis and Russia's military activity in the Baltic Sea region, Finland and Sweden are currently engaged in an intensive debate about their national security. Faced with a changing threat scenario, there is growing doubt in both countries about their current defence capabilities. Questions are also being asked about the security policy course pursued since the end of the Cold War, with calls for higher military spending and NATO accession being the reflex response. However, corresponding initiatives would need to be embedded in a comprehensive and coherent security and defence strategy. Various options for cooperation exist at bilateral, regional and European level and could comprise key elements of this strategy. (SWP Comments)
Keywords: 320